Shape-persistent (4+4) imine cages with a truncated tetrahedral geometry - Lauer, Jochen; Rominger, Frank; Mastalerz, Michael (Chemistry - a European journal, 2018)
The synthesis of shape-persistent organic cage compounds is often based on the usage of multiple dynamic covalent bond formation (such as imines) of readily available precursors. By careful choice of the precursors geometry, the geometry and size of the resulting cage can be accurately designed and indeed a number of different geometries and sizes have been realized to date. Despite of this fact, little is known about the precursors conformational rigidity and steric preorganization of reacting functional groups on the outcome of the reaction. Herein, the influence of conformational rigidity in the precursors on the formation of a [4+4] imine cage with truncated tetrahedral geometry is discussed.